The Role of Perceived Usefulness, Facilitating Conditions and Subjective Norms on Intention to Subscribe Digital On-Demand Streaming Service Netflix - Nurdiani, Tanti Widia; Safari, Apay; Kusnadi, Iwan Henri; Riyanti, Anti; Sari, Dina Fahma; Pramono, Susatyo Adhi (Yayasan Gema Bina Nusantara, 2025)
An important factor in the success of a business is the performance of the promotion and marketing team. Management does everything to attract the attention and interest of potential buyers and also loyal customers. Digitalization and globalization have resulted in a massive number of producers, products and services. This study aims to analyze the influence of the variables perceived usefulness, facilitating conditions and subjective norms on the intention to subscribe to Netflix on-demand streaming service. The researcher conducted descriptive and verification analysis, where the researcher tested the effect of each independent variable on the dependent variable. The results of the analysis show that all independent variables have a positive effect on the dependent variable, namely the intention to subscribe. The researcher suggests that management continue to innovate Netflix services, be it the team's service in the field, good response from customer service and the quality of movies that continues to improve. This aims to create a good perception of the benefits of using Netflix services. The suggestion for the government is to continue to improve digital infrastructure to support the growth of digital-based businesses in Indonesia.